HEGEMONI GRAMSCI DAN PRAKTIK KEAGAMAAN HABAIB DI INDONESIA - Muhammad Rizky Shorfana; Aswar Aswar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This study underscores the pressing need to comprehend the religious practices of habaib in Indonesia within the conceptual framework of Antonio Gramsci's hegemony theory. This phenomenon can be attributed to the profound socio-religious influence of Habaib within Indonesian Muslim society. habaib is frequently regarded not only as a descendant of the Prophet Muhammad, but also as a moral and spiritual authority. This perspective prompts inquiries into the mechanisms through which cultural hegemony can be established by means of religious practices that are transmitted across generations. The present study aims to critically examine how Habaib religious practices, such as maulid, haul, and pilgrimage, act as tools of hegemony within the framework of civil and political society as understood by Gramsci. The methodological approach employed in this study is a qualitative one, incorporating a library research method, with a focus on the analysis of primary and secondary sources pertinent to the theoretical framework of hegemony and the historical context of Habaib. The results of this study demonstrate two significant conclusions. Firstly, Habaib religious practices function as a means of consensus building through symbolic domination in civil society. Secondly, Habaib's position as traditional intellectuals enables them to maintain cultural domination without the use of coercive power. This study demonstrates that religious practices function not only as spiritual activities, but also as a strategic instrument in the process of shaping and maintaining hegemony within Indonesian Muslim society. Key Word: Antonio Gramsci, Hegemony, Habaib